Proses Stamping Press Pembuatan Part Bracket Harness - Rifky Riansyah; Rizki Achmad Darajatun (Peneliti.net, 2022)
PT. Ichii Industries Indonesia is a dies stamping company that produces auto parts. PT. Ichii Industries Indonesia is related to the production process where the company's goal is to run the production process, PT. Ichii Industries Indonesia makes a good and correct production process in order to create quality products that can continue to be marketed and produced sustainably or do not stop production. Therefore it is necessary to know about the process of making good parts in accordance with the company's SOP. In an industry, the production process must run smoothly in order to produce quality products that can be said to be part in a condition of zero defects or no defects, how to make the product not experience defects, of course, must implement strict supervision or control during the production process